Anterograde Colonic Stent Placement via a Cecostomy Tube Site - Lawrence M Gillman; Steven Latosinsky (Canadian Journal of Gastroenterology)
Colonic stents have been used as a method of relieving colonic obstruction since 1991. They are classically inserted in a retrograde fashion via the rectum and are deployed under a combination of endoscopic and fluoroscopic guidance. A unique case is presented where the colonic stent was passed in an anterograde fashion through a recently created cecostomy tube site as a method of palliation to relieve an obstructing hepatic flexure tumour.